Pemahaman Tentang Kasus Kekerasan Seksual Pada Anak Dan Perempuan Dengan Melakukan Kegiatan Sosialisasi Berprogram Pengabdian Masyarakat Di Desa Kalisemo - Tsalaatsa ‘Ashri Harsandi; Dicky Dewa Kurniawan; Mike Elly Anitasari (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2024)
Sexual violence against children and women is a serious problem in the social realm that often occurs in Indonesia regarding community development. This affects the well-being of individuals and society at large. This study uses qualitative methods, in the form of (1) Observations of PKK women in Kalisemo Village as mobilizers of women in Kalisemo village, Loano as well as subjects in this research (2) Women's empowerment socialization activities with psychology student resource persons. This study analyzes forms of sexual violence against children and women, the characteristics of children when they occur and are identified, the impact of sexual violence, factors that cause sexual violence, and forms of preventing sexual violence. The importance of awareness of sexual violence against children and women requires comprehensive action from various parties, including the government, non-governmental organizations, the general public, and family support to prevent this problem effectively.